Analisa Pemberian Kompensasi terhadap Kinerja Karyawan di PT Surya Toto Indonesia - Santoso, Mohamad; Hefniwati, Ella; Dewi, Cynthia; Septiani, Kurnia Rahmah; Supratikta, Hadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In an era of increasingly intense business competition, employee performance has become a crucial factor in enhancing a company's productivity and competitiveness. This study aims to analyze the influence of the compensation system on employee performance at PT Surya Toto Indonesia, a manufacturing company specializing in sanitation products. The research adopts a qualitative approach to gain an in-depth understanding of the relationship between compensation and employee performance. The object of the study is the compensation system implemented in the company, including base salary, position allowances, tenure-based pay, education incentives, and overtime compensation. Informants were selected purposively and consisted of employees from various levels and departments, including human resources personnel, supervisors, and operational staff. Data were collected through in-depth interviews using open-ended questions and supported by documentation analysis, such as internal policy documents and performance reports. The data analysis process involved data reduction, data display, and conclusion drawing through thematic analysis. The findings reveal that the compensation system is designed fairly and transparently, and serves as a key motivator for employees, positively influencing their performance, job satisfaction, and loyalty to the company. The study concludes that appropriate and comprehensive compensation not only boosts employee productivity but also strengthens professionalism within the organization, making it a strategic element in maintaining competitive advantage.